The generation of carcinogenic etheno-DNA adducts in the liver of patients with nonalcoholic fatty liver disease - Linhart, Kirsten-Berit; Glassen, Katharina; Peccerella, Teresa; Waldherr, Rüdiger; Linhart, Heinz; Bartsch, Helmut; Seitz, Helmut K. (Hepatobiliary surgery and nutrition, 2015)
Nonalcoholic fatty liver disease (NAFLD), in particular its more aggressive form nonalcoholic steatohepatitis (NASH) is increasingly observed as a cause of end stage liver disease and hepatocellular carcinoma (HCC). Reactive oxygen species (ROS) are an important factor in the pathogenesis of HCC. ROS can react with polyunsaturated fatty acids derived from membrane phospholipids resulting in the production of reactive aldehydes as lipid oxidation (LPO) byproducts, such as 4-hydroxynonenal (4 HNE). 4 HNE can react with DNA to form mutagenic exocyclic etheno-DNA adducts. ROS is induced by inflammatory processes, but also by induction of cytochrome P450 2E1 (CYP2E1), as seen with chronic alcohol consumption.